Bioenergy carbon capture storage and utilization: a critical review of market dynamics and policy implications - Singh, Dig Vijay; Nagappan, Senthil; Lay, Chyi-How; Igliński, Bartłomiej; Piechota, Grzegorz; Kumar, Gopalakrishnan; Parra-Saldívar, Roberto; Kumar, Vinod (Springer, 2026)
Bioenergy with carbon capture, utilization, and storage (BECCUS) is a competent technology with the potential to address global climate change challenges. However, its deployment faces significant hurdles across technological, economic, and policy domains. The production of biofuels including ethanol, methane, butanol, and biogas is accompanied by the release of carbon dioxide (CO2). This CO2 can be incorporated into organic molecules through various biochemical routes as part of the metabolic mechanisms of carbon absorption. The efficiency of these carbon assimilation pathways can be improved through ongoing developments in metabolic engineering, which can increase the production of valuable bioproducts, improve carbon sequestration, and support efforts to mitigate climate change. The present review recognizes critical avenues for advancing BECCUS, emphasizing market mechanisms, technological innovations, and cross-sector integration in both developed and developing countries such as India. The review recommends policy modifications aimed at establishing a transparent framework related to carbon pricing, emission trading systems, and proper certification mechanisms for biogenic carbon utilization. These modifications, coupled with the integration of renewable energy systems, would not only stimulate BECCUS adoption, but also foster its economic feasibility and sustainability. Additionally, promising technologies such as chemical looping and microalgae-based carbon capture should be technologically scaled up to ensure industrial-level applications. The integration of BECCUS with other sectors is also critical to optimize the impact of this technology on climate change mitigation. Therefore, the present review highlights the need for a robust policy framework, technology-driven innovation, and cross-sector research collaboration to resolve the challenges associated with BECCUS, boost its adoption, and ensure its economic feasibility and environmental sustainability. Moreover, providing regulatory support, augmenting market competitiveness, and aligning research on BECCUS play a transformative role in attaining the goals of the Paris Agreement and promoting environmental sustainability.Graphical Abstract
Keywords: 31 Biological Sciences; 3106 Industrial Biotechnology; 13 Climate Action; 7 Affordable and Clean Energy; 15 Life on Land; Biomass; Bioenergy; CO2; Carbon capture and storage; BECCUS; Market; Policy framework